Coordination-Driven Self-Assembly of M(3)L(2) Trigonal Cages from Pre-organized Metalloligands Incorporating Octahedral Metal Centers and Fluorescent Detection of Nitroaromatics - Wang, Ming (2011)
The design and preparation of novel M(3)L(2) trigonal cages via coordination-driven self-assembly of pre-organized metalloligands containing octahedral aluminum(III), gallium(III), or ruthenium(II) centers is described. By employing tritopic or dinuclear linear metalloligands and appropriate complementary subunits, M(3)L(2) trigonal-bipyramidal and trigonal prismatic cages are self-assembled under mild conditions. These 3-D cages were characterized with multinuclear NMR spectroscopy ((1)H and (31)P) and high-resolution electronic spray mass spectrometry (HR-ESI-MS). The structure of one such trigonal prismatic cage, self-assembled from an arene ruthenium metalloligand, was confirmed via single-crystal X-ray crystallography. The fluorescent nature of these prisms, due to the presence of their electron-rich ethynyl functionalities, prompted photophysical studies which revealed that electron-deficient nitroaromatics are effective quenchers of the cages' emission. Excited state charge transfer from the prisms to the nitroaromatic substrates can be used as the basis for developing selective and discriminatory turn-off fluorescent sensors for nitroaromatics.